Growth Hormone–Releasing Hormone Agonists Reduce Myocardial Infarct Scar in Swine With Subacute Ischemic Cardiomyopathy. Issue 4 (April 2015) - Bagno, Luiza L.; Kanashiro‐Takeuchi, Rosemeire M.; Suncion, Viky Y.; Golpanian, Samuel; Karantalis, Vasileios; Wolf, Ariel; Wang, Bo; Premer, Courtney; Balkan, Wayne; Rodriguez, Jose; Valdes, David; Rosado, Marcos; et al.
Abstract : Background: Growth hormone–releasing hormone agonists (GHRH‐As) stimulate cardiac repair following myocardial infarction (MI) in rats through the activation of the GHRH signaling pathway within the heart. We tested the hypothesis that the administration of GHRH‐As prevents ventricular remodeling in a swine subacute MI model. Methods and Results: Twelve female Yorkshire swine (25 to 30 kg) underwent transient occlusion of the left anterior descending coronary artery (MI). Two weeks post MI, swine were randomized to receive injections of either 30 μg/kg GHRH‐A (MR‐409) (GHRH‐A group; n=6) or vehicle (placebo group; n=6). Cardiac magnetic resonance imaging and pressure–volume loops were obtained at multiple time points. Infarct, border, and remote (noninfarcted) zones were assessed for GHRH receptor by immunohistochemistry. Four weeks of GHRH‐A treatment resulted in reduced scar mass (GHRH‐A: −21.9±6.42%; P =0.02; placebo: 10.9±5.88%; P =0.25; 2‐way ANOVA; P =0.003), and scar size (percentage of left ventricular mass) (GHRH‐A: −38.38±4.63; P =0.0002; placebo: −14.56±6.92; P =0.16; 2‐way ANOVA; P =0.02). This was accompanied by improved diastolic strain. Unlike in rats, this reduced infarct size in swine was not accompanied by improved cardiac function as measured by serial hemodynamic pressure–volume analysis. GHRH receptors were abundant in cardiac tissue, with a greater density in the border zone of the GHRH‐A group compared with the placebo group. Conclusions: Daily subcutaneous administration of GHRH‐A is feasible and safe in a large animal model of subacute ischemic cardiomyopathy. Furthermore, GHRH‐A therapy significantly reduced infarct size and improved diastolic strain, suggesting a local activation of the GHRH pathway leading to the reparative process.